Effect of Calcium Pre-rinse and Fluoride Dentifrice on Enamel and on Dental Plaque Formed In Situ - Furlani, Tatiana Almeida; Magalhaes, Ana Carolina; Iano, Flavia Godoy; da Silva Cardoso, Vanessa Eid; Delbem, Alberto Carlos Botazzo [UNESP]; Rabelo Buzalaf, Marilia Afonso (Quintessence Publishing Co Inc, 2009)
Purpose: The aim of this in situ double-blind randomised crossover study was to investigate the effect of calcium (Ca) pre-rinse on the composition of plaque and on enamel prior to the use of fluoride (F) dentifrice.Materials and Methods: During four phases (14 days each) of this study, 10 volunteers had agreed to wear dental appliances containing two healthy bovine enamel blocks. A fresh solution containing 20% weight/volume (w/v) sucrose was dripped on the enamel blocks ex vivo for 5 min three times a day. Subsequently, the appliances were replaced in the mouth, and the volunteers rinsed their mouth with 10 mL of a Ca (150 mmol/L) or a placebo rinse (1 min). In sequence, a slurry (1:3 w/v) of F (1030 ppm) or placebo dentifrice was dripped onto the blocks ex vivo for 1 min. During this time, the volunteers brushed their teeth with the respective dentifrice. The appliances were replaced in the mouth, and the volunteers rinsed their mouth with water. The plaque formed on the blocks was analysed for F and Ca. The enamel demineralisation as well as the incorporation of F on enamel was evaluated by cross-sectional microhardness and alkali-soluble F analysis, respectively. Data were tested using analysis of variance (P < 0.05).Results: The Ca pre-rinse prior to the use of the F dentifrice led to a three- and sixfold increase in the plaque F and Ca concentrations, respectively. It also did not have any additive effect on the F content on the enamel and the demineralisation of the enamel, in comparison with the use of F dentifrice alone.Conclusions: A Ca lactate rinse used prior to the F dentifrice was able to change the mineral content in the plaque, but it was unable to prevent enamel demineralisation.
Keywords: calcium; dental enamel; dental plaque; fluoride dentifrice; in situ